8x-11=-3x-4

Simple and best practice solution for 8x-11=-3x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-11=-3x-4 equation:


Simplifying
8x + -11 = -3x + -4

Reorder the terms:
-11 + 8x = -3x + -4

Reorder the terms:
-11 + 8x = -4 + -3x

Solving
-11 + 8x = -4 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-11 + 8x + 3x = -4 + -3x + 3x

Combine like terms: 8x + 3x = 11x
-11 + 11x = -4 + -3x + 3x

Combine like terms: -3x + 3x = 0
-11 + 11x = -4 + 0
-11 + 11x = -4

Add '11' to each side of the equation.
-11 + 11 + 11x = -4 + 11

Combine like terms: -11 + 11 = 0
0 + 11x = -4 + 11
11x = -4 + 11

Combine like terms: -4 + 11 = 7
11x = 7

Divide each side by '11'.
x = 0.6363636364

Simplifying
x = 0.6363636364

See similar equations:

| 5(X-1)=10-2(3X+2) | | 3x^2-12x(1.5)= | | 5+.5c=14 | | 2(x-5)-x=-6 | | 72-5x=13x+20 | | 6+5n=9-2n | | 0.07x*0.03=0.38 | | 1.4(a+6)=2.8(a+10) | | -97-8x=60-22x | | 112=1.5s | | 6x(2x+7)= | | 9+3(-7y+1)=6(y+7)+6 | | 50+65+x=505 | | 4x-3=7x+18 | | 6x(2x-7)= | | 9x=14x-21 | | -7x+11=19-x | | 3+10n=12n-3 | | 0-5x=6x+19 | | (y/4)=-10 | | g(x)=x^2-2X+5 | | x^3+3sinx+2cosx=2 | | 85-6x=w | | 2-5y=18 | | 3x-7+4=28 | | 2432+42= | | 5x+2+4x=7+2x-4 | | 2432+4= | | 2(3x+2)-4(3x-1)=-4 | | 4x^2-5x+9=7x+4 | | 20w^2-9w=0 | | 3(3x+4)=5(-x+2) |

Equations solver categories